Unsupervised colour segmentation of white blood cell for acute leukaemia images - A. S., Abdul Nasir; Mohd Yusoff, Mashor, Prof. Dr.; H., Rosline (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/